Health care professionals’ perspectives on the utilisation of a remote surveillance and care tool for patients with COVID-19 in general practice: a qualitative study - Hoffmann, Mariell; Stengel, Sandra; Szecsenyi, Joachim; Peters-Klimm, Frank (BMC primary care, 2022)
Most COVID-19 patients with severe symptoms are treated in hospitals. General practices are responsible for assessing most ambulatory patients. However, they face several challenges managing COVID-19 patients, and those with non-COVID-19 conditions. In April of 2020, we designed a software tool for the structured surveillance of high-risk home-quarantined COVID-19 patients in general practice (CovidCare) including several telephone monitorings, in order to support general practices and early identification of severe courses. This study presents the qualitative results of a mixed-methods process evaluation study on CovidCare.
Gesehen am 19.10.2022